Daytime Sky Quality at El Leoncito, Argentina - Iglesias, F. A. (2023)
We characterize the daytime sky quality in terms of brightness, cloud coverage, and main weather variables at the Carlos Ulrico Cesco station of the Felix Aguilar Astronomical Observatory (OAFA), located in El Leoncito National Park, San Juan, Argentina. We have collected more than 15 years of daily observations from the auxiliary sky brightness detectors of the Mirror Coronagraph for Argentina (MICA, in operations from 1997 to 2012), including daily observing reports. We additionally present data from two meteorological stations operated at the site from 2000 to 2020. We determine the main statistical properties and seasonal variability of daytime sky brightness, clear sky time fraction (CSTF), precipitable water vapor (WV), temperature, humidity, and wind speed, which are relevant for solar, particularly coronal observations. Our results confirm that El Leoncito is an excellent place to perform daytime astronomical observations. We measure a median sky brightness of 15.8 ppm, estimated at 526.0 ± 1.0 nm and 6 solar radii from the solar disk center; a median CSTF of 0.7; and a median WV below 6 mm. These values, and those of other relevant weather variables, are comparable to the levels found among the best astronomical observing sites in the world. Due to the extended period of time analyzed and high sampling frequency, the novel data and results presented in this report contribute to the analysis and interpretation of historical sky brightness data and are of great value for the future planning of daytime astronomical instrumentation at El Leoncito.